2019
DOI: 10.1111/hsc.12788
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and treatment needs among the Juang tribe-a particularly vulnerable tribal group residing in Northern Odisha, India: A cross-sectional study

Abstract: The study was aimed to assess the oral health status and treatment needs of Juang tribe residing in Bansapal taluk of Northern Odisha. A cross‐sectional survey was carried out among 1,412 Juangs using a cluster random sampling procedure. Bansapal taluk is subdivided into six Gram Panchayat's (GP) with each GP considered as a cluster. From each of the six GP's, equal number of villages was chosen randomly using lottery method in order to get uniform representation. A total of 16 villages were chosen using this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This is much higher than the prevalence of leukoplakia among the Paniya tribes of Kerala which was 1.90% [ 9 ]. Similarly, in contrast to our study, the prevalence of Tobacco Pouch keratosis (4.8%) was much higher among Juang tribes of Odisha [ 20 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is much higher than the prevalence of leukoplakia among the Paniya tribes of Kerala which was 1.90% [ 9 ]. Similarly, in contrast to our study, the prevalence of Tobacco Pouch keratosis (4.8%) was much higher among Juang tribes of Odisha [ 20 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in the present study, the Irula tribes had a higher mean DMFT (6.58 ± 3.99) than the Narikuvar tribe (5.30 ± 3.160). This is not surprising given that Irulars, one of the particularly vulnerable tribal groups (PVTGs) defined by the Indian government, are known for their enduring backwardness, which is shown in their subpar standard of life, eating habits, health, and hygiene [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the older age groups, the greatest need was for ‘fissure sealants’. Another study conducted by Das et al ,[ 17 ] also showed that the children of Juang tribal was characterized by high prevalence of dental caries and high treatment needs.…”
Section: Discussionmentioning
confidence: 99%
“…74,76,79,80 Of extreme importance, especially in dealing with a community where orthodontic treatment is yet to make in roads, is to be able to very clearly elicit patient preferences related to treatment to avoid treatments sought just to satisfy psychological or sociopsychological needs rather than true somatic needs. 81 Extensive studies have been performed to assess the self-perceived oral health status and self-perceived esthetics as related to the prevalence of malocclusion but these studies rely on the clinical interpretation of the investigator with no simple way of eliciting a young adolescent's response, thus not truly eliciting informed consent from the adolescent with the main involvement of only the clinician and a parent or guardian. 50,[82][83][84][85][86][87][88][89][90][91][92] The World Health Organization indicates the need for any index to be simple, reliable, reproducible, and accurate enough to cater to the screening of large groups of individuals.…”
Section: Discussionmentioning
confidence: 99%